2013
DOI: 10.1016/j.ijid.2013.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Severe sepsis caused by a linezolid-resistant Enterococcus faecium in a 10-year-old girl after multiple trauma

Abstract: While infections caused by Enterococcus faecium resistant to vancomycin (VRE) are increasing, linezolid-resistant strains are still rare. We present the case of a 10-year-old girl with severe sepsis caused by a linezolid-resistant E. faecium (Van-B VRE) after multiple trauma and right-sided hemipelvectomy. The off-label use of a targeted antimicrobial therapy with daptomycin (350 mg/day; approximately 8 mg/kg) for 17 days resulted in rapid normalization of infection parameters and improved clinical status. No … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 6 publications
0
6
0
3
Order By: Relevance
“…Resistance is gradually increasing among enterococci. Especially the number of vancomycin resistant pediatric cases is gradually increasing (8,9). In a seven-year study conducted by Çelebi et al (10), the prevalence of VRE was reported to be 1-15% and vancomycin resistance for Enterococcus spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resistance is gradually increasing among enterococci. Especially the number of vancomycin resistant pediatric cases is gradually increasing (8,9). In a seven-year study conducted by Çelebi et al (10), the prevalence of VRE was reported to be 1-15% and vancomycin resistance for Enterococcus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Linezolid has been approved for use in treatment of community acquired and nosocomial pneumonia and skin and soft tissue infections (1 (1,9).…”
Section: Discussionmentioning
confidence: 99%
“…[13] Thus far, there are only two drugs approved by the FDAt ot reat specifically vancomycinresistant enterococcal infections.L inezolid, an oxazolidinone-based antibiotic is known to inhibit VRE isolates with am inimal inhibitory concentration (MIC) value of 0.75 to 4 mgmL À1 whereas quinupristin/dalfopristin is only active on Enterococcus faecium strains,w ith comparable MIC values reported in the literature (Figure 1). [14] Polycyclic polyprenylated acylphloroglucinols (PPAPs) are compounds of plantal origin and mostly isolated from representatives of the Clusiaceae family. [15][16][17][18] Their core structure contains ab icyclo[3.3.1]nonane-2,4,9-trione that is substituted with av ariety of unsaturated side chains ( Figure 1).…”
mentioning
confidence: 99%
“…[13] Es wurden fürd ie Va ncomycin-resistenten Stämme E. faecalis VRE366 und E. faecium VRE392 MIC-Werte von unter 4 mgmL À1 beobachtet, die vergleichbar mit denen der Standardantibiotika Linezolid und Quinupristin/Dalfopristin bei VRE-Infektionen sind. [14] Streptococcous pneumoniae ATCC49619 wurde in Konzentrationsbereichen, die vergleichbar zu denen von Va ncomycin sind (MIC(23) = 0.5 mgmL À1 ,M IC(Vancomycin) = 0.25 mgmL À1 )i nhibiert.…”
unclassified
“…Die Verbindungen 1, 9, 10, 12, 20 und 21 zeigten IC 50 -Werte im Bereich von 4b is 20 mgmL À1 ,g efolgt von den allylierten Verbindungen 22 (223 mgmL À1 )u nd 14 (82 mgmL À1 ), ebenso wie den dreifach isoprenylierten Verbindungen 23 (96 mgmL À1 )u nd 19 (145 mgmL À1 [13] Es wurden fürd ie Va ncomycin-resistenten Stämme E. faecalis VRE366 und E. faecium VRE392 MIC-Werte von unter 4 mgmL À1 beobachtet, die vergleichbar mit denen der Standardantibiotika Linezolid und Quinupristin/Dalfopristin bei VRE-Infektionen sind. [14] Streptococcous pneumoniae ATCC49619 wurde in Konzentrationsbereichen, die vergleichbar zu denen von Va ncomycin sind (MIC(23) = 0.5 mgmL À1 ,M IC(Vancomycin) = 0.25 mgmL À1 )i nhibiert.…”
unclassified